The status of the translation profession in the European Union - Pym, Anthony 1956-; Sfreddo, Claudio; Grin, François (Anthem Press, 2014)
Based on thorough and extensive research, this book examines in detail traditional status signals in the translation profession. It provides case studies of eight European and non-European countries, with further chapters on sociological and economic modelling, and goes on to identify a number of policy options and make recommendations on rectifying problem areas